Elevated mean platelet volume to platelet ratio predicts advanced fibrosis in chronic hepatitis C. Issue 4 (April 2020) - Gozdas, Hasan Tahsin; Ince, Nevin
Abstract : Objective: Chronic hepatitis C virus (HCV) infection is an important health problem that can cause liver cirrhosis and hepatocellular carcinoma. Recently, novel inflammatory markers from complete blood count have been used as a precursor of many clinical conditions. In this study, we investigated the role of hemogram parameters in predicting advanced liver fibrosis in chronic HCV patients. Methods: Patients who underwent percutaneous liver biopsy due to chronic HCV infection between 01.01.2011 and 01.08.2019 were included in this study. Liver biopsies were evaluated according to Ishak method. Patients were classified into those with mild fibrosis (F ⩽ 2) and advanced fibrosis (F ≥ 3). Hemogram parameters of these groups were compared and their efficacy in predicting severe fibrosis was investigated. Results: Of the 81 chronic HCV patients, 38 cases were in the mild fibrosis group and 43 cases were in the severe fibrosis group. Mean platelet volume, mean platelet volume to lymphocyte ratio, mean platelet volume to platelet ratio, and red cell distribution width to platelet ratio of the severe fibrosis group were significantly higher than those of the mild fibrosis group ( P < 0.05 for all). In the ROC curve analysis, mean platelet volume to platelet ratio showed the biggest area under the curve in the prediction of advanced fibrosis. Conclusion: Mean platelet volume to platelet ratio may be an easy and practical biomarker to gain a preliminary insight into advanced fibrosis in chronic HCV patients.